Measuring Consumer Perceptions of Business Ethical Behavior in Two Muslim Countries - Tsalikis, J. (Journal of business ethics, 2009)
After measuring consumers’ sentiments toward business ethical practices in mostly Christian countries, the Business Ethics Index was expanded to two Muslim countries – Turkey and Egypt. The overall BEI for both countries was on the negative range, with Egypt exhibiting the widest gap between personal ethical perceptions and vicarious ones. No difference between genders was observed.